Preprocessing of fingerprint images captured with a digital camera - Hiew,, B. Y; Teoh, , Andrew B. J.; Ngo, ., David C. L (2006)
Reliable touch-less fingerprint recognition still remains a challenge nowadays as the conventional techniques that used to preprocess the optical or capacitance sensor acquired fingerprint image, for segmentation, enhancement and core point detection, are inadequate to serve the purpose. The problems of the touch-less fingerprint recognition are the low contrast between the ridges and the valleys in fingerprint images, defocus and motion blur. However, it imposes a competency for a further advancing of this biometric modality since it frees from the problems in terms of hygienic, maintenance and latent fingerprints. In this paper, the digital camera is opted as the device to capture the fingerprint image in RGB format and the procedures to segment, enhance and detect the core point of the fingerprint image are outlined.